Evaluating the efficiency of Mediterranean container ports using data envelopment analysis. Issue 3 (September 2021) - Fancello, Gianfranco; Serra, Patrizia; Aramu, Valentina; Vitiello, Daniel Mark
Mediterranean container ports are constantly requested to face new market challenges after years of decline of their traffic in favour of a stronger leadership of Northern range ports, also favoured by the consolidation of the Arctic Route and the Belt and Road Initiative. To regain competitiveness, Mediterranean ports must undertake a path of operational, managerial and infrastructural strengthening. This study applies Data Envelopment Analysis (DEA) to 35 Mediterranean container ports in order to identify the potential key success factors on which to intervene to improve their competitiveness potential and response to the new market needs. The application uses the port throughput as output, and three inputs: yard area, number of quay cranes and distance of the port from the Suez–Gibraltar axis. The latter has been inserted in the study to evaluate whether it can affect port efficiency. Both input- and output-oriented approaches are used in order to investigate the port competitiveness through the production function (input-oriented), and the port commercial competitiveness based on the output and feasibility of its production (output-oriented). Results can provide insights for the implementation of future policies and management strategies aimed to strengthen the Mediterranean port context.